UPAYA PENYELESAIAN TERHADAP WANPRESTASI DALAM LAYANAN JASA FOTOGRAFI DI KOTA PADANG - Yunanda Sukma; Jasman Nazar (JOURNAL OF LAW AND NATION, 2024)
Examining default in photographic service agreements in Padang City and attempts to address it are the goals of this study. In the rapidly expanding field of wedding and event photography, disputes between clients and vendors sometimes result in defaults. Defaults might take the form of untimely payments, inconsistent outcomes, or unilateral cancellation. Using primary data from interviews and secondary data from regulatory and literature analysis, this study employs normative methodologies. The findings demonstrate that weaker written and verbal agreements are typically the cause of defaults. Usually, non-litigation methods like discussion and notification are used to settle default; going to court is the final resort. The purpose of this study is to advance knowledge and offer suggestions for the resolution of defaults in photography services, assisting legislators, attorneys, and